SOME ISSUES OF RESPONSIBILITY OF MANAGEMENT BODIES OF JOINT-STOCK COMPANIES - Khachikyan, Martin (State and Law, 2022)
The article is devoted to the corporate liability of joint-stock companies as a separate type of civil liability. The responsibility of corporate governance bodies is understood as the legal responsibility that a member (members) of the board of directors, a director (executive director), a member (members) of the council and directorate, a managing organization and a head bear for their actions and decisions. In other words, if any of the entities exercising corporate governance does not fulfill its obligations or does it negligently, then this body is liable both to this joint-stock company and to its stakeholders for the damage caused to them. Identification of the specifics of the responsibility of corporate governance bodies and the allocation of grounds for liability arising from other obligations is aimed at ensuring a clear and effective resolution of disputes arising in corporate legal relations, as well as clarifying the circumstances that should be discussed when making a decision on compensation for the damage caused. This article discusses the legislation of the Republic of Armenia, which regulates the responsibility of corporate governance bodies of joint-stock companies, the legislation of a number of foreign countries, judicial practice and the approaches of various jurists. In particular, there was discussed the need for a special legal qualification regarding the responsibility of management bodies in corporate relations and the clarification of the circumstances holding the liability of bodies of joint-stock companies.